Building an Instrument by Generating a Function - Aytemiz, Y. (Open Schools Journal for Open Science, 2020)
Building a musical instrument requires precise calculations of the positions of its holes to obtain desired notes. To make these calculations, sound waves should be examined. Sound is a longitudinal wave and has five distinguishing aspects: amplitude, frequency, wavelength, period, and speed. A note is characterized by the frequency of the wave. In this experiment, the frequencies of notes and the speed of sound in air is used to calculate the length of a closed-end tube needed to obtain that frequency. Then, these values of lengths are used to create sound and the frequencies are measured with a tuner. The water level is changed until the desired frequency is reached. Then, a graph of length and 1/frequency is drawn to experimentally determine the slope, from which a function of length of tube is written in terms of frequency. With this equation, length required for any note can be calculated.